Distinguishing German Residential and Commercial Tenancy Law: Are Tenant and Landlord in an Equal Position? - Christin Eissing (Udayana Journal of Law and Culture, 2023)
The German housing market, particularly in major cities, is very tight. This situation makes Tenancy Law the issue that has attracted the most attention in local and federal elections. This article presents and illustrates various methods of protecting the individual parties to a lease contract. Besides, it highlights the differences between Residential Tenancy Law and Commercial Tenancy Law and explains why legislation distinguishes between these two types of tenancies. This research establishes arguments and interpretations from relevant laws and regulations, including the German Civil Code and German General Equal Treatment Act, and judicial decisions that clarified the legal relations between tenants and landlords. This article concludes that Tenancy Law in Germany distinguishes in different ways between Residential Tenancy Law and Commercial Tenancy Law from legal, social, and economic perspectives. It also infers that the provisions stipulated in German Tenancy Law protect the tenant's right while remaining attractive for landlords to offer the house(s) for rent.